PENGARUSUTAMAAN GENDER DALAM PENGELOLAAN HAJI DI KOTA PONTIANAK - Rahmaniah, Syarifah Ema (KARSA: Journal of Social and Islamic Culture, 2015)
To organize pilgrimage (hajj) has been a national task involving multi-institutions both in Indonesia and in Saudi Arabia. The Indonesion government is obliged to accelerate the quality of pilgrimage organization in forms of the service of registration administration, manasik advisory, pilgrimage trip, travel documents, air and land transportations, medic, accommodation, food, and security. The study identifies several problems in the pilgrimage management, such as finance and service problems that are not transparent, fair, participative, long waiting list, transportation, accommodation, and the problem of managements that is not responsive genderCopyright (c) 2015 by KARSA. All right reservedDOI:Â 10.19105/karsa.v23i1.611Â